Book Review: True Colors by Jay Mauerer and Irene Schoenberg - Luis Fernando Gómez (Asociación Colombiana de Profesores de Ingles, 2016)
In what follows I will provide an analysis of what may be called the general environment of the textbook. Basically four questions concerning the environment of the materials will be examined, namely: view of language, methodology, learner role and teacher role. The central question here is to find out if the environment created by the material promotes effective language learning. The evaluation process, then, helps us gain a better understanding of what is effective, what is less effective, and what appears to be of no use at all.